Islamic Ceramics and Rural Economy in the Trapani Mountains during the 11th century - Sacco, Viva; Testolini, Veronica; Martin Civantos, José Maria; Day, Peter M. (Journal of Islamic Archaeology, 2020)
Located in the Trapani Mountains of North-West Sicily, the hilltop site of Pizzo Monaco has formed the focus of systematic excavation and an innovative, integrated study of the total ceramic assemblage, as part of the MEMOLA FP7 project. The date, provenance and production technology of the varied types of pottery are investigated by macroscopic, morphological and decorative analysis, in combination with petrography and scanning electron microscopy in order to assess social, technological and economic ties of this rural site and its environs with the early Islamic capital of Sicily at Palermo, the wider island and North Africa. Local production of cooking vessels is compared with glazed and plain storage pottery, serving and consumption vessels from Palermo, in a region where the new relationship between coastal centre and nearby mountain economies was being forged. Correlation of the properties of the pottery assemblage with the unusual architecture suggests the storage of a repeated ceramic set, perhaps on a household basis, in a site which may be a fortified storage facility, rather than sustaining more permanent occupation. The typological study provides new information on the range of ceramics circulating in Sicily during the mid-11th century CE, revealing the full spectrum of ceramics consumed at this time. This approach contrasts with work that privileges a view of simple transmission of glazing technologies across the Islamic Mediterranean. Indeed a comparison of production sequences in the crafting of similar glazed bowls at Palermo demonstrates the co-existence of different communities of practice and cautions against over-simplified reconstructions of the transmission of glazing technologies in the early medieval Mediterranean. The range of pottery available from a variety of sources highlights the consumption choices made by these communities in the medieval period.